EDUCATION ACTIVITIES OF THE AMERICAN PEACE CORPS IN TURKEY - Gökhan EŞEL (Fırat University, 2020)
The Peace Corps first appeared as a promise to the university youth, just before the presidental election in the USA acquired on the year of 1960 , by Kennedy. It began to act after John F. Kennedy had become the president of the USA. Peace Corps was shaped by effecting of the methods, experiences, programmes and procedures of many institutions that were set up before in the USA. The goals of the Peace Corps were stated at the speeches during the election and public addresses after the establisment of the organization as, “to introduce the USA to the other nations, to know more about them, to assure less-developed countries a supreior quality of labor concerning their social and economical progress”. As a matter of fact, Peace Corps Volunteers started coming to Turkey, according to the agreement between the USA and Turkish Government that was signed in 1962. The activities of Peace Corps were supressed for the political, social and negative reactions of the public opinion. So the Peace Corps left Turkey in 1971.